Prevalence and Genetic Analysis of Thalassemia and Hemoglobinopathy in Different Ethnic Groups and Regions in Hainan Island, Southeast China - Wang, Min; Zhang, Xiaozhuang; Zhang, Yubin; Xiao, Meifang (Frontiers in Genetics, 2022)
Background: There are limited studies on the molecular profile of thalassemia in Hainan, the free trade island in China. Our aim was to reveal the prevalence and molecular mutation spectrum of thalassemia in different ethnic groups and regions of Hainan through a large sample study for the first time. Methods: A total of 231,596 individuals from 19 cities and counties in Hainan were screened by hematological parameter analysis, and further genetic analysis was performed on individuals with MCV less than 82 fL. Results: Totally, 31,780 (13.72%) subjects were diagnosed as thalassemia carriers. The overall prevalence of α-thalassemia, β-thalassemia, and α+β-thalassemia were 11.04%, 1.48%, and 1.20%, respectively. We further analyzed the molecular profiles of thalassemia in various ethnic groups and mainly compared the difference between Han and Li. The results showed that the frequency of thalassemia in the Li population (47.03%) was much higher than that in Han (9.37%). Except for β-thalassemia (1.31% of Li vs. 1.47% of Han), the frequencies of α-thalassemia (39.59% of Li vs. 7.35% of Han) and α+β-thalassemia (6.13% of Li vs. 0.56% of Han) in the Li were obviously higher than those in Han. The high-frequent genotypes of α-thalassemia in Han were αα/--SEA (25.55%), -α3.7/αα (22.17%), -α4.2/αα (21.59%), αWSα/αα (8.93%), and -α3.7/-α4.2 (4.17%) and those of Li were -α4.2/αα (17.24%), -α3.7/αα (17.16%), -α3.7/-α4.2 (15.09%), αWSα/αα (9.69%), and αWSα/-α3.7 (8.06%), respectively. The αα/--SEA was the highest genotype of α-thalassemia in Han but only accounted for 1.87% in Li. For β-thalassemia, the top three high-frequent genotypes in both Han and Li were βCD41/42(-TTCT)/βN, β-28(A>G)/βN, and βIVS-Ⅱ-654(C>T)/βN, but the frequency of βCD41/42(-TTCT)/βN in Li (90.96%) was much higher than that in Han (56.32%) and the data reported in other provinces of China. Additionally, the prevalence of thalassemia ranged from 8.16% to 34.35% in Hainan, Wuzhishan, Baoting, Qiongzhong, and Baisha have a higher prevalence than other areas. Conclusion: Our study revealed the characteristics of ethnic and regional differences in the prevalence of thalassemia in the childbearing age population of Hainan for the first time, indicating that the prevalence of thalassemia among Li nationality is the highest in China. Those findings will be useful for genetic counseling and the prevention of thalassemia.